Faktor Penyebab dan Upaya Penanggulangan Penggunaan Bahan Peledak dalam Pencurian Ikan di Perairan Laut Sawu, Kabupaten Kupang - Alfin Kadja; Rudepel Petrus Leo; Deby F. Ng. Fallo (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine and explain the factors causing the use of explosives in fish theft in the waters of the Sawu Sea, Kupang Regency and also to determine and explain the countermeasures against the use of explosives in fish theft in the waters of the Sawu Sea, Kupang Regency. This research is a qualitative study with empirical or sociological legal research methods and the object of research is causal factors and countermeasures. Data collection using interview techniques and literature study. The data analysis technique used is qualitative descriptive technique. The results of this study show that there are six factors causing the use of explosives in fish theft in the waters of the Sawu Sea, Kupang Regency, namely: (1) weak legal awareness factor, (2) motive factor, (3) weak economic factor, (4) weak law enforcement factor, (5) weak supervision factor, and (6) difficult to detect crime scene factor. Countermeasures carried out by the police and government agencies are premitive efforts, namely initial efforts made by competent government parties to provide appeals to avoid criminal acts. Preventive efforts are efforts made to provide prevention of community action both social problems and crime so as not to reach the threshold of disturbance and become a real disturbance. Repressive efforts are efforts made by competent parties when there has been a criminal offense or crime whose actions are in the form of law enforcement by imposing penalties.